Pelaksanaan Fungsi Manajemen: Permasalahan dan Solusi (Studi di Koperasi Simpan Pinjam Bangun Mandiri) - Perkasa, Ripho Delzy; Amalia, Rafiqah; Dalimunthe, Nona Zanuwariska; Rizky, Muhammad Fadlan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to identify the problems faced by the Bangun Mandiri Savings and Loans Cooperative (KSP) and the solutions implemented to overcome them. Through a qualitative case study approach and in-depth interviews with three cooperative employees, four main problems were found: (1) borrowers stopped working; (2) the borrower runs away; (3) employees embezzle funds; and (4) low profits. KSP Bangun Mandiri addresses problems with a proactive approach, including flexible policies, communication with related parties, as well as evaluation and system updates. The research results show that through the comprehensive implementation of Planning, Organizing, Actuating and Controlling (POAC) management functions, cooperatives can maintain business continuity amidst various challenges. These findings offer insight into the internal dynamics of KSP and practical guidance for effective KSP management.